2015
DOI: 10.1038/leu.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride antileukemic activity in acute promyelocytic leukemia is GSK-3 and MEK/ERK dependent

Abstract: We recently identified that the MEK/ERK1/2 pathway synergized with retinoic acid (RA) to restore both transcriptional activity and RA-induced differentiation in RA-resistant acute promyelocytic leukemia (APL) cells. To target the MEK/ERK pathway, we identified glycogen synthase kinase-3β (GSK-3β) inhibitors including lithium chloride (LiCl) as activators of this pathway in APL cells. Using NB4 (RA-sensitive) and UF-1 (RA-resistant) APL cell lines, we observed that LiCl as well as synthetic GSK-3β inhibitors de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
(58 reference statements)
3
12
0
1
Order By: Relevance
“…SOR applied to APL cells has been reported to reduce the number of cells [3,[16][17][18][19]. Consistent with our findings, lithium preventing carcinogenesis in APL cells and various cell lines has also been seen in current studies in the literature [20,21,15]. The effect of increasing apoptosis was stronger than the effect of decreasing total cell count.…”
Section: Discussionsupporting
confidence: 91%
“…SOR applied to APL cells has been reported to reduce the number of cells [3,[16][17][18][19]. Consistent with our findings, lithium preventing carcinogenesis in APL cells and various cell lines has also been seen in current studies in the literature [20,21,15]. The effect of increasing apoptosis was stronger than the effect of decreasing total cell count.…”
Section: Discussionsupporting
confidence: 91%
“…Even though the basis for the discrepancy with our results is unclear, accumulated research has shown that the outcome in cell proliferation can be cell type-, context- and stimulus-dependent. An anti-mitogenic action of lithium has been reported primarily in cancer cells from colon, neuroblastoma and leukemia [5456]. In normal cells, on the contrary, both the action of lithium and that of GSK-3β inhibitors has been prevalently linked to an increase rather than a decrease in cell proliferation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Even though LiCl is widely used experimentally, the molecular mechanisms by which LiCl treatment regulates ERK phosphorylation have not yet been elucidated, various different responses having been obtained depending on the type of cell studied (Ref. 36).…”
Section: Discussionmentioning
confidence: 99%